Yahoo Web Search

related to K.C

1. Sort by

1. If y=K/X n is a power to X, the independant value is??? A. y B. k C. X D. N?

ans : [ X ] ------

1 Answers Ā· Science & Mathematics Ā· 24/05/2010

2. how would I prove that an equation involving combinations are equal?

k*C(n+1,k) = k * (n+1)!/(k!(n+1-k)!) = (n+1)!/((k-1)!(n+1-k)!) = (n+1) * n!/((k-1)!(n+1-k)!) = (n+1) * C(n, k-1)

1 Answers Ā· Science & Mathematics Ā· 14/08/2007

3. Can you help me find the first and second derivative?

Use the Quotient Rule. = [1-e^(-alpha(u)] [k+(c)(lamba)] - [k+(c)(lamda)(u)) (-e^(-alpha(u)) (-alpha)] / (1-e^(-alpha)(u)]^2 Note...

1 Answers Ā· Science & Mathematics Ā· 27/03/2008

4. Prove using a combinatorial arguments?

n * C(n-1, k-1) = n * [(n-1)! / ((k-1)! (n-k)!)] = n! / ((k-1)! (n-k)!) = k * [n! / (k! (n-k)!)] = k * C(n, k). I hope this helps!

1 Answers Ā· Science & Mathematics Ā· 20/11/2011

5. Solve the recursive relation by finding a closed-form formula and vice versa?

Note that c_k - c_{k-1} = 2k. The sum of (c_k - c_{k-1}) from k=1 to n is (c_n - c...

3 Answers Ā· Science & Mathematics Ā· 21/03/2008

6. algebra Math problems help?

4x + 7 - 9x = 9 4x - 9x = 9 - 7 -5x = 2 x = -2/5 = -0.4

1 Answers Ā· Science & Mathematics Ā· 16/04/2011

7. Matrix question?

... A and B are in K(C) Xt (A+B) X = (... C X^N will be in K(C) by induction. But you can realise...

2 Answers Ā· Science & Mathematics Ā· 22/10/2007

8. i really need help with math problems please?

1) if log k= c log v + log p, what is the value of k? start with the RHS: two ...

2 Answers Ā· Science & Mathematics Ā· 31/03/2008

Ę(k) = ā[k + (k ā c)^2], assuming c is a constant, and k is the only variable. Ę...v, by chain rule, we get: Ę'(k) = u' ā v ā u^(v - 1) Ę'(k) = [1 + 2(k ā c)] ā 1/2 ā [k + (k ā c)^2]^(-1/2) Ę'(k) = (1 + 2k ā 2c) / (2ā[k + (k ā c...

3 Answers Ā· Science & Mathematics Ā· 23/02/2013

10. How to prove this combinatoric identity?

Pascal's rule: C(n,k) = C(n-1,k) + C(n-1, k-1) First, show...m!n!) out the window to get sum [k=0 to n] (-1)^k * C(n, k) = 0 which again can be shown easily by...

2 Answers Ā· Science & Mathematics Ā· 30/07/2009